Optimization of Electrical Energy Consumption in Multi-Storey Government Buildings Using Smart Building Systems - Syahrin Syahrin; Abdul Multi; Lilly S. Wasitova (International Journal of Advanced Multidisciplinary, 2026)
Multi-storey government buildings generally exhibit high electrical energy consumption, particularly in heating, ventilation, and air conditioning (HVAC), lighting, and supporting electrical equipment. Conventional operational patterns that do not adapt to occupancy levels and environmental conditions often lead to significant energy inefficiencies and increased operational costs. In recent years, smart building technologies have been recognized as an effective approach to improving energy performance in non-residential buildings. This study aims to optimize electrical energy consumption in a multi-storey government building through the implementation of a Smart Building System based on a Building Energy Management System (BEMS). The research adopts an applied case study approach conducted at a provincial government office building in Indonesia. The methodology includes an energy audit, analysis of electrical load profiles, evaluation of energy performance indicators, and comparison of energy consumption before and after the application of BEMS-based optimization strategies. The results demonstrate a measurable reduction in total electricity consumption, peak load demand, and operational electricity costs, while maintaining acceptable indoor comfort conditions. The findings confirm that the application of smart building systems can significantly enhance energy efficiency in government buildings and provide a practical framework for sustainable energy management in the public sector.